2011
DOI: 10.1177/1753193411420033
|View full text |Cite
|
Sign up to set email alerts
|

Expansile aneurysmal bone cyst in the tubular bones of the hand treated with en bloc excision and autograft reconstruction: a report of 12 cases

Abstract: Primary aneurysmal bone cysts (ABCs) in the small tubular bones of the hands are rare and optimal treatment is not yet established. Between August 1997 and June 2009, 12 patients with biopsy-proven expansile primary ABCs of the small tubular bones of the hand were treated with en bloc tumor excision and strut autograft reconstruction. The adjacent joint was preserved if feasible, otherwise it was fused. Patients were followed for at least 2 years (mean = 7 years). All grafts were incorporated except for partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Risk of local recurrence may be as high as 60 percent when treated with curettage and bone grafting alone. 7,39 Adjuvant treatments such as liquid nitrogen, argon laser, cement, burring, and liquid nitrogen may decrease recurrence rates to less than 20 percent 15,39,40 and should be considered in the presence of articular surface involvement, complete bony involvement, or recurrent lesions. 4,41 Liquid nitrogen should be used with caution in skeletally immature patient because of the risk of premature physeal closure.…”
Section: Aneurysmal Bone Cystsmentioning
confidence: 99%
“…Risk of local recurrence may be as high as 60 percent when treated with curettage and bone grafting alone. 7,39 Adjuvant treatments such as liquid nitrogen, argon laser, cement, burring, and liquid nitrogen may decrease recurrence rates to less than 20 percent 15,39,40 and should be considered in the presence of articular surface involvement, complete bony involvement, or recurrent lesions. 4,41 Liquid nitrogen should be used with caution in skeletally immature patient because of the risk of premature physeal closure.…”
Section: Aneurysmal Bone Cystsmentioning
confidence: 99%
“… 5 , 6 Recently, Jafari et al observed a case of local recurrence in a series of patients treated in the same manner. 7 Similarly, many independent authors have reported a 100% local control rate in the patients that were treated with complete resection of the ABC. 8-11 …”
Section: En Bloc Surgical Excisionmentioning
confidence: 94%